The human multidrug resistance-associated protein MRP is a plasma membrane drug-efflux pump. - Zaman, G J (1994)
The multidrug-resistance associated protein MRP is a 180- to 195-kDa membrane protein associated with resistance of human tumor cells to cytotoxic drugs. We have investigated how MRP confers drug resistance in SW-1573 human lung carcinoma cells by generating a subline stably transfected with an expression vector containing MRP cDNA. MRP-overexpressing SW-1573 cells are resistant to doxorubicin, daunorubicin, vincristine, VP-16, colchicine, and rhodamine 123, but not to 4'-(9-acridinylamino)methanesulfon-m-anisidide or taxol. The intracellular accumulation of drug (daunorubicin, vincristine, and VP-16) is decreased and the efflux of drug (daunorubicin) is increased in the transfectant. The decreased accumulation of daunorubicin is abolished by permeabilization of the plasma membrane with digitonin, showing that MRP can lower the intracellular daunorubicin level against a concentration gradient. Anti-MRP antisera predominantly stain the plasma membrane of MRP-overexpressing cells. We conclude that MRP is a plasma membrane drug-efflux pump.